1992
DOI: 10.1128/jb.174.16.5457-5461.1992
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding specificity and sequence of Xanthomonas campestris catabolite gene activator protein-like protein

Abstract: The Xanthomonas campestris catabolite gene activator protein-like protein (CLP) can substitute for the Escherichia coli catabolite gene activator protein (CAP) in transcription activation at the lac promoter (V. de Crecy-Lagard, P. Glaser, P. Lejeune, O. Sismeiro, C. Barber, M. Daniels, and A. Danchin, J. Bacteriol. 172:5877-5883, 1990). We show that CLP has the same DNA binding specificity as CAP at positions 5, 6, and 7 of the DNA half site. In addition, we show that the amino acids at positions 1 and 2 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
3
26
0
1
Order By: Relevance
“…Using mutant sequences of the E. coli lac promoter as substrates, Clp has been shown to have the same DNA-binding specificity as CRP at positions 5, 6 and 7 (GTG motif) of the DNA half-site (Dong & Ebright, 1992). In our previous studies with the Xcc engA promoter, site-directed mutagenesis also indicated that the GTG motif of the proposed Clp core consensus sequence is essential for both DNA-protein complex formation in vitro and engA gene expression in vivo (Hsiao et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Using mutant sequences of the E. coli lac promoter as substrates, Clp has been shown to have the same DNA-binding specificity as CRP at positions 5, 6 and 7 (GTG motif) of the DNA half-site (Dong & Ebright, 1992). In our previous studies with the Xcc engA promoter, site-directed mutagenesis also indicated that the GTG motif of the proposed Clp core consensus sequence is essential for both DNA-protein complex formation in vitro and engA gene expression in vivo (Hsiao et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Using mutant sequences of the E. coli lac promoter as the substrates, the X. campestris Clp has been shown to have the same DNA binding specificity as CRP at positions 5, 6, and 7 (GTG motif) of the DNA half site [26]. Two consensus Clp-binding sites with a spacer of 27 nt were present at nt À80 to À59 (site I, centered at À69.5) and À53 to À32 (site II, centered at À42.5) relative to TIS (Fig.…”
Section: The Enga Upstream Region Possesses Two Clp-binding Sitesmentioning
confidence: 99%
“…engA promoter resembles class II CRP-dependent promoter except the presence of tandem Clp sites and a much shorter spacer than those of tandem CRP sites The amino acid residues that contact DNA base pairs in CRP-DNA complex are R180 and E181 in CRP, which are conserved in Clp, R201 and E202 [26]. The residues (A156, M157, T158, H159, P160, D161, and G162) in CRP making direct protein-protein interaction with the E. coli RNA polymerase a subunit C-terminal domain (aCTD) in transcription activation are also highly conserved in Clp (A177, M178, S179, H180, P181, Q182, and G183) [26,28,29]. The amino acids similar to the region in E. coli RNA polymerase aCTD (T285, E286, V287, E288, L289, G315, R317 and L318) responsible for interaction with CRP are also found in the X. campestris RNA polymerase aCTD (T284, E285, V286, E287, L288, G314, K316 and L317) [26,28,29].…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Data represent means ± SD of three experiments engXCA promoter [9]. The DNA sequence for Clp binding has been evaluated and found to be similar to that of the E. coli CRP-binding site (5 0 -AAATGTGA-TCTAGA-TCACATTT-3 0 ) [4]. This binding site is 22 bp in length and exhibits perfect twofold sequence symmetry, with the bold-type bases representing the left and right sites each for the binding of one subunit of the active CRP dimer [15].…”
Section: Clp Regulated Transcription Of Xpse Gene Through Directly Bimentioning
confidence: 99%